2016
DOI: 10.1103/physrevd.94.126011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical boundary for anti–de Sitter space

Abstract: We argue that a natural boundary condition for gravity in asymptotically AdS spaces is to hold the renormalized boundary stress tensor density fixed, instead of the boundary metric. This leads to a well-defined variational problem, as well as new counter-terms and a finite on-shell action. We elaborate this in various (even and odd) dimensions in the language of holographic renormalization. Even though the form of the new renormalized action is distinct from the standard one, once the cut-off is taken to infin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 55 publications
0
29
0
1
Order By: Relevance
“…Since the structure of these terms is such that the variations are acted on by covariant derivatives one cannot impose the Dirichlet condition. For this reason one adds an extra term of the trace of the second fundamental formoften called the Gibbons-Hawking term [12] (see [13,14] for reviews; discussions on the Dirichlet boundary conditions can also be found, e.g., in [15][16][17][18][19][20][21]) -in the starting action so that the variation of the extra term exactly cancels the boundary terms above. It is then possible to impose the Dirichlet boundary condition.…”
Section: Classical Boundary Conditionmentioning
confidence: 99%
“…Since the structure of these terms is such that the variations are acted on by covariant derivatives one cannot impose the Dirichlet condition. For this reason one adds an extra term of the trace of the second fundamental formoften called the Gibbons-Hawking term [12] (see [13,14] for reviews; discussions on the Dirichlet boundary conditions can also be found, e.g., in [15][16][17][18][19][20][21]) -in the starting action so that the variation of the extra term exactly cancels the boundary terms above. It is then possible to impose the Dirichlet boundary condition.…”
Section: Classical Boundary Conditionmentioning
confidence: 99%
“…Note however that attractor behavior is typically associated to uncharged scalars, so the flavor here is slightly different. One can also try to construct hairy solutions with other boundary conditions (see eg., [39][40][41]). …”
Section: Jhep11(2016)041mentioning
confidence: 99%
“…There is thus no incompatibility between the Kounterterms and the usual Dirichlet boundary condition, because δg (0) ij = 0 indeed implies δK i j = 0 at the required level of accuracy. (Other works have explored the viability of different boundary conditions for ALAdS gravity, of Neumann [88][89][90][91] or Robin [92] type. )…”
Section: Introductionmentioning
confidence: 99%